Monitoring Of Agricultural Lands Using Geoinformation Technologies - Pardayeva Sevinch Shuhrat kizi (Zien Journals, 2024)
In this article, the main purpose of agricultural land monitoring with the help of Geoinformation technologies, Geographic Information Systems (GIS), areas of application of GIS in agriculture in Uzbekistan were studied.
Keywords: Geoinformation systems; land monitoring; agriculture